Cholesteric liquid crystal biosensor platform with image analysis for rapid detection of COVID-19 - Lin, Ping-Yuan; Chung, Yi-Wei; Chuang, Er-Yuan; Wang, Yen-Chieh; Lai, Min-Chih; Hsu, Yen-Chin; Lin, Chun-Che; Hsiao, Yu-Cheng (Frontiers in Bioengineering and Biotechnology, 2023)
Rapid and low-cost diagnosis of coronavirus disease 2019 (COVID-19) is essential to identify infected subjects, particularly asymptomatic cases, primarily to arrest the spread of the disease through local transmission. Antibody-based chromatographic serological tests, as an alternative to the RT-PCR technique, offer only limited help due to high false positives. We propose to exploit our cholesteric liquid crystal biosensor platform for one-step, wash-free, rapid detection of the severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) virus directly with minimal sample pre-processing. As mentioned above, cholesteric liquid crystals are an effective and innovative approach to health care as a rapid test for the diagnosis of COVID-19 and other diseases.